Evaluation of The Knowledge Levels of Religious Officials About The Basic Opinions of The Religious Sects in Terms of Different Variables - Altın, Muhammed Emin; Kubat, Mehmet (Fırat University, 2024)
Religion, as a phenomenon that is as old as humanity, has continued to exist in one way or another wherever humans exist. At the core of religion are the principles of faith consisting of divinity, belief in the afterlife and belief in prophethood. When we look at the History of Religions, in almost all religions, when religion first emerged, there was no need for any institution to maintain religious life in a healthy way, but in later periods, protecting religion against attacks from outside, responding to new demands, 'socialization', which are important tasks in social life. The need for institutional organization has emerged for reasons such as being able to fulfill issues such as 'distributing justice' and 'managing religious rites' in a regular and orderly manner, meeting the need to resolve disputes between people through religious means, increasing its followers and encountering different cultures by spreading over wide geographies. All religions have established some institutions to meet these needs. In today's Turkey, in order to respond to the religious needs of the Muslim community and to ensure continuity in religious services without creating any institutional gaps, the Presidency of Religious Affairs, today known as the Presidency of Religious Affairs, was established within the budget of the Prime Ministry and affiliated to the Prime Ministry, with Law No. 429. The Presidency of Religious Affairs has been fulfilling its duties related to the principles of worship, morality and belief, which are the three basic components of the Islamic religion, in line with the objectives specified in the law, without interruption since the day it was established. In the history of Islamic thought, sects are evaluated in two categories: fiqh-practical and religious-political. Firstly, sects whose religious aspects came to the fore were formed. The beginning of the formation of sects such as Hanafi, Maliki, Shafi and Hanbali, which are called fiqh sects and talk about the rules and principles of worship and how to perform worship, coincides with the second century of Hijri and later periods. It is extremely important that religious officials who provide religious services to people of all ages and strata have a reasonable level of knowledge on theological issues as well as their knowledge of practical/fiqh sects. Religious officials, affiliated with DIB, provide multi-dimensional religious services in many different areas, especially mosques and Quran courses. In Turkish society, the most important source of information about religious issues for a large segment of the population is either the imam hatip or muezzin trustee in the neighborhood mosque, the Quran course instructor in the Quran course, or the preachers they reach through different channels such as 190 alo. In line with the information they receive, their religious perceptions are shaped and they continue their religious lives. In this study, it is aimed to reveal the basic views of religious sects and their knowledge levels of religious officials, who have a very important impact on shaping the religious lives of large masses of people. The study group of the research consists of religious officials working in the religious services class working under the Malatya provincial mufti between September 2020 and February 2021. The sample group of the research consists of 401 religious officials working as preachers, Quran course instructors, imam hatip and muezzin trustees under the Malatya provincial mufti's office. The method used in the research was simple random sampling, where each officer had an equal chance. The main purpose of simple random sampling is; The aim is to obtain more objective data by including each individual in the universe with an equal chance in the sample group. In the study, data was obtained with a two-part survey form prepared by the researcher by paying attention to all necessary stages. Both content analysis and descriptive analysis were used to analyze the data obtained. The data was collected by sending a survey link to the participants via Google form due to force majeure conditions arising from the pandemic. Additionally, official permissions were received from the Presidency of Religious Affairs. The collected data was transferred to the SPSS program and interpreted by subjecting it to various tests and was presented visually through tables. As a result of the study, the findings were interpreted by comparing them with similar and opposing studies, and at the end, some suggestions were given for both researchers and practitioners. At the end of the research, it was understood that the level of knowledge of the religious officials who participated in the research regarding the basic views of the theological sects, even if it was at an acceptable level for some sects, was generally not at the expected level and that they did not have sufficient bookish knowledge.

Din konusu insanlıkla yaşıt olan bir olgu olarak insanın var olduğu her yerde öyle veya böyle varlığını sürdürmüştür. Dinin temelinde özünde ulûhiyet, ahiret inancı ve nübüvvet inancının oluşturduğu iman esasları yer alır. Dinler Tarihine bakıldığında neredeyse bütün dinlerde dinin ortaya ilk çıktığı dönemde dini hayatın sağlıklı bir şekilde sürdürülmesi için herhangi bir kuruma ihtiyaç duyulmamışken daha sonraki dönemlerde dini dışardan gelen hücumlara karşı korumak, oluşan yeni taleplere cevap vermek, toplum hayatında üstlendiği önemli görevler olan “sosyalleştirme”, “adalet dağıtma” ve “dini ayinleri yönetme” gibi hususları düzenli ve kurallı bir biçimde yerine getirebilmek, insanlar arasındaki anlaşmazlıkları dini yolla çözümlenme ihtiyacını gidermek, müntesiplerinin artması ve geniş coğrafyalara yayılarak farklı kültürlerle karşılaşması gibi sebeplerle kurumsal örgütlenme ihtiyacı ortaya çıkmıştır. Bütün dinler söz konusu bu ihtiyaçları gidermek üzere bazı kurumlar ihdas etmişlerdir. Günümüz Türkiye’sinde de Müslüman toplumun dinî gereksinimlerine cevap vermek ve din hizmetlerinde herhangi bir kurumsal boşluğa mahal vermeden devamlılığı sağlamak amacıyla 429 Sayılı Kanun’la, Başvekâlet bütçesi dâhilinde ve Başvekâlete bağlı Diyanet İşleri Reisliği, bugünkü adıyla Diyanet İşleri Başkanlığı kurulmuştur. Diyanet İşleri Başkanlığı, yasalarda belirtilen hedefler doğrultusunda üzerine aldığı İslâm dininin üç temel bileşeni olan ibadet, ahlak ve inanç esasları ile ilgili vazifeleri icra etme görevini kurulduğu günden bugüne kadar aksatmadan yerine getirmektedir. İslam düşünce tarihinde mezhepler fıkhi-ameli ve itikâdî-siyasi olmak üzere iki kategoride değerlendirilmektedir. İlk olarak itikâdî yönü ön plana çıkan mezhepler teşekkül etmiştir. Fıkhî mezhepler olarak isimlendirilen ve ibadetlerin kural ve kaidelerinden, ibadetlerin nasıl yapılacağından bahseden Hanefi, Maliki, Şafi ve Hanbeli ve gibi mezheplerin teşekkül etmeye başlaması ise, hicri ikinci asır ve daha ileriki dönemlere denk gelmektedir. Her yaştan her tabakadan insana din hizmeti sunan din hizmetleri sınıfında görev yapan din görevlilerinin amelî/fıkhî mezhepler hakkındaki bilgileri yanında itikâdî konulardaki bilgi düzeylerinin makul bir düzeyde olması son derece önem arz etmektedir. Din görevlileri Diyanet İşleri Başkanlığına bağlı olarak başta camiler ve Kur’an kursları olmak üzere çok farklı alanlarda çok boyutlu din hizmeti sunmaktadırlar. Türkiye toplumunda halkın büyük bir kesimi dini konularla ilgili en önemli bilgilenme kaynağı ya mahalle camisindeki imam hatip veya müezzin kayyım ya da Kur’an kursundaki Kur’an kursu öğreticisi ya da alo 190 gibi farklı kanallarla ulaştığı vaizler olmaktadır. Aldıkları bu bilgiler doğrultusunda din algıları şekillenmekte ve dini hayatlarını sürdürmektedirler. Bu çalışmada geniş halk kitlelerinin dini hayatlarının şekillenmesinde çok önemli etkileri olan din görevlilerinin itikâdî mezheplerin temel görüşleri ile bilgi düzeylerinin ortaya çıkarılması amaçlanmıştır. Araştırmanın çalışma grubunu 2020 Eylül ayı ile 2021 Şubat ayları arasında Malatya il müftülüğüne bağlı olarak çalışan din hizmetleri sınıfında görev yapan din görevlileri oluşturmaktadır. Araştırmanın örneklem grubunu ise Malatya il müftülüğüne bağlı olarak vaiz, Kur’an kursu öğreticisi, imam hatip ve müezzin kayyım kadrolarında görev yapan 401 din görevlisi oluşturmaktadır. Araştırmada yöntem her görevlinin eşit şansa sahip olduğu basit seçkisiz örneklem kullanılmıştır. Basit seçkisiz örneklemde temel amaç; evrende yer alan her bir bireyin eşit bir şansa sahip olarak örneklem grubuna dâhil edilerek daha objektif veriler elde edilmesidir. Araştırmada veriler araştırmacı tarafından gerekli bütün aşamalara dikkat edilerek hazırlanmış iki bölümden oluşan anket formu ile elde edilmiştir. Elde edilen verilerin analizinde ise hem içerik analizi hem de betimsel analizden yararlanılmıştır. Veriler pandemi şartlarında oluşan mücbir şartlardan dolayı Google form üzerinden katılımcılara anket linki gönderilmek suretiyle toplanmıştır. Anketin uygulanması için ilgili kuruldan etik raporu alınmıştır. Ayrıca Diyanet İşleri Başkanlığı’ndan resmi izinler alınmıştır. Toplanan veriler spss programına aktarılmış ve çeşitli testlere tabi tutularak yorumlanmış ve tablolar yoluyla da görsel olarak sunulmuştur. Çalışma sonucunda ise elde edilen bulgular benzer ve karşıt çalışmalarla karşılaştırılarak yorumlanmış ve sonunda hem araştırmacılar hem de uygulayıcılar için bazı önerilere yer verilmiştir. Araştırma sonunda araştırmaya katılan din görevlilerinin itikâdî mezheplerin temel görüşlerine ilişkin bilgi düzeylerinin, bazı mezhepler için kabul edilebilir düzeyde olsa bile, genel olarak beklenen düzeyde olmadığı, yeterli kitabi bilgiye sahip olmadıkları anlaşılmıştır
Din Görevlilerinin İtikâdî Mezheplerin Temel Görüşleri İle İlgili Bilgi Düzeylerinin Farklı Değişkenler Bakımından Değerlendirilmesi
Keywords: Islamic Sects; İslam Mezhepleri; Kalam; Kelam